The Effect of Inquiry Learning Model on Mathematical Ability Connection And Habit of Mind of Eighth-Grade Students at MTs Ma’arif NU 09 Kutawis Purbalingga - Hidayah, Hawa; Ulpah, Maria (UM Purwokerto Press, 2025)
Mathematical connection ability and habit of mind are essential aspects of mathematics learning; however, they remain low among eighth-grade students at MTs Ma’arif NU 09 Kutawis. Conventional learning methods tend to be less effective in encouraging students to think critically and connect mathematical concepts. The inquiry learning model is believed to enhance these aspects by actively engaging students in exploration and problem-solving processes. This study aims to determine the effect of the inquiry learning model on students' mathematical connection ability and habit of mind. The research method used was a quasi-experimental design with a Nonequivalent Control Group Design. The study sample consisted of two classes: the experimental class, which applied the inquiry learning model, and the control class, which implemented teacher centered learning -based instruction. Data were collected through mathematical connection tests and habit of mind questionnaires, then analyzed using the N-Gain Score to assess mathematical connection ability and habit of mind. The results showed a positive effect of the inquiry learning model on students’ mathematical connection ability and habit of mind. The average N-Gain in the experimental class for mathematical connection was 0.723 (high category), while in the control class, it was 0.46 (medium category). For habit of mind, the average N-Gain in the experimental class was 0.5 (medium category), whereas in the control class, it was 0.416 (medium category). Thus, the improvement in students’ mathematical connection ability and habit of mind in the experimental class was higher than in the control class.